Resenha: TREVISAN, Dalton. Rita Ritinha Ritona. Rio de Janeiro: Record, 2005. (Revista do Centro de Estudos Portugueses, 2005)
Resenha: TREVISAN, Dalton. Rita Ritinha Ritona. Rio de Janeiro: Record, 2005.